GNSS data acquired during the 2021-2022 unrest at Station VCOA - Alessandro Bonforte; Gianpiero Aiesi; Francesco Calvagna; Salvatore Consoli; Lucia Pruiti; Alessio Rubonello; Benedetto Saraceno (PANGAEA, 2023)
At the end of the summer 2021, an increase in CO2 emissions at Vulcano brought to an increase in the alert level and, as a consequence, to the upgrade of the monitoring activities by increasing the number of instruments deployed and the rate of the surveys. One of the new devices installed was a geodetic GNSS mobile network for a Real-Time and High-Frequency monitoring of ground deformation, to increase the detail with respect to the existing permanent network. The whole dataset provided here, consists of 1022 files for a total of 13GB of GNSS RINEX raw data. The GNSS data archive is organized in 4 folders, one for each station, named with the site abbreviation (namely, VCAM, VCOA, VCST and VPRT). Within each folder, there are all the raw data files for that station, one for each day of acquisition. Names of the files are structured following the RINEX 3 standard, the first 4 digits being the station code, that is an S and the last 3 digits of the receiver serial number. The date of acquisition is given by the 11 digits in the central part of the name, in the format YYYYDDDHHMM; namely, 4 digits for the year, followed by 3 digits for the day of the year (from 1 to 365 or 366 for leap years) and then 2 digits for the hour and 2 for the minute of the starting time.
In: Bonforte, A et al. (2023): GNSS data acquired during the 2021-2022 unrest at Vulcano island (Italy) by the Real-Time Mobile Network [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963930